(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
Children throughout their lives will always be influenced by family, school, and society at large. The family environment is the first and foremost educational environment for children who provides guidance and examples for children. This study aims to determine the effect of family environmental conditions on the learning interest of fifth grade students at SDN Semanan 08 Pagi. The research method used is a quantitative research method. The type of approach used is a correlational approach. The data collection technique used in this research is using a questionnaire. Based on the results of data analysis that has been carried out, it is concluded that the family environment has a significant effect on the learning interest of fifth grade students at SDN Semanan 08 Pagi. The resulting influence has a positive direction. It can be seen in the coefficient test of the determination of the family environment on interest in learning, the value of R = 0.577 indicates that there is a relationship between the family environment and positive interest in learning. While the R Square of 0.333 gives the understanding that learning interest is influenced by the family environment by 33.3% while the rest (100% - 33.3% = 66.7%) is the contribution of other variables outside the variables studied by researchers